Studding the effect of gluons exchange interaction on the pressure and phase diagram of quark – gluons plasma (Latakia University Journal -Basic Sciences Series, 2018)
In this work we have studied the effect of exchange interactions between the gluons of order  on the pressure and phase diagram of quark – gluon plasma, where we have studied both of them as function of temperature and chemical potential, and we assumed that, the plasma composed of just two massless quarks (the up and down quark) which exchange interaction.The bag model has been used, where the bag B and coupling  constants were assumed to be independent of temperature and chemical potential. We have found that the gluons interactions of order  had a negative effect on the pressure of the plasma, which cause the quarks to stay in the  confined phase, and then increases the critical temperature where the hadrons dissolve to  quarks and gluons. We have showed that, the results depend strongly on the values of both the coupling and bag constants which had been used.